Idiosyncratic volatility vs. liquidity? Evidence from the US corporate bond market - Kalimipalli, Madhu; Nayak, Subhankar (Journal of Financial Intermediation, 2012)
Our objective in this paper is to determine empirically the extent to which fixed-income investors are concerned about the relative effects of equity volatility and bond liquidity in the cross-section of corporate bond spreads. Our tests reveal that while both volatility and liquidity effects are significant, volatility, representing ex-ante credit shock, has the first-order impact, and liquidity represented by bond characteristics and price impact measure has the secondary impact on bond spreads. Conditional analysis further reveals that distressed bonds and distress regimes are both associated with significantly higher impact of volatility and liquidity shocks. However, the relative impact of these effects varies conditional on the underlying bond attributes and overall market conditions.